Williams Brass (comp.). Biological Aspects of Demography, Symposia of the Society for the Study of Human Biology, vol. 10. Londres, Taylor and Francis Ltd., 1971. 167 p. - Ordorica, Manuel (Estudios Demográficos y Urbanos, 1971)
WILLIAM BRASS (comp.) Biological Aspects of Demografhy, Symposia of the Society for the Study of Human Biology, Vol. 10. Londres, Taylor y Francis Ltd., 1971.